KAJIAN PENGGUNAAN OBAT BERDASARKAN INDIKATOR WORLD HEALTH ORGANIZATION (WHO) DI UPTD PUSKESMAS SUNGAI APIT - Sinata, Novia; Rahimi, Indari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Pharmaceutical care in hospitals is essential to patient therapy. The WHO estimates that 50% of drug use is irrational, including improper prescription, production, and sales. This study uses WHO prescribing indicators to describe drug use at Sungai Apit UPTD in 2023. Descriptive observational research using retrospective technique. The research population was 14,400 2023 Sungai Apit Health Center UPTD prescription papers. The research sample was selected via proportionate random sampling. 150 prescription pages were sampled. The study's WHO prescribing indicators showed the percentage of generic drug prescriptions (96.341%), antibiotic prescriptions (12.667%), injection preparation prescriptions (6%), the average number of drug items per prescription sheet (2.733), and National Formulary drug prescriptions (91.219%). In conclusion, the Sungai Apit Health Center UPTD's 2023 average parameter of drug items per prescription sheet and National Formulary medicine prescriptions does not match WHO prescription indicators.Keywords: Prescription, Drugs, Health Center, WHO.